Perfil clínico-epidemiológico, sorológico e molecular da hanseníase em área endêmica potiguar - Silveira, Ismênia Glauce de Oliveira Barreto da (2017)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae and persists as a serious public health problem in Brazil. The fact that this microorganism is inculcable makes it difficult to diagnose and elucidate details of its transmissive chain. Aiming to clarify the role of house dust in the disease transmission route, this case-control study carried out in the Barrocas, Mossoró, RN, Brazil, the largest cluster in the state, compared clinical, epidemiological, slit skin smear and serological results of 22 newly diagnosed patients of the cluster, with molecular results of detection of the specific RLEP and 16S rRNA genomic regions of this bacillus in the nasal swab samples, saliva and house dust of these individuals and of the controls (44 household contacts and 44 endemic contacts) between november 2015 to november 2016. There was greater detection in women and school-age youth, with degree of disability, with predominance of paucibacillary forms. There was no statistical difference between the number of BCG vaccine scars from patients and endemic contacts, and 31.8% of the patients had no vaccine scar. The two rapid serological tests evaluated, ML-flow and OrangeLife® presented similar results, with a higher positivity among paucibacillary patients through the latter (54.5%). Both were superior to slit skin smear (9.1%). Regarding molecular research, the positivity in nasal swab and saliva of multibacillary patients with primer RLEP was 16.7% and 33.3%, respectively. There was no detection of bacterial DNA in domestic dust or between paucibacillary. Regarding the DNA analysis in saliva of endemic multibacillary contacts, there was 27.2% positivity. Associating molecular and serological results, it was possible to identify 4.5% of subclinicity between home contacts and 15% of asymptomatic carrier status. Regarding the risk variables, residing in dwellings with up to two windows offered 3.79 times more chance of progressing to this outcome, having a history of cases of leprosy in the family increased 2.89 times the risk of presenting seropositivity by the OrangeLife® serological test In this community and being over 60 years of age gave 3.6 times more chances of having positive serological reaction for leprosy with the test evaluated, which denotes prolonged exposure to the bacillus. Although not statistically significant, it was noted that the pattern of low schooling, low income, environmental insalubrity, population agglomeration and inadequate living habits made up a sociodemographic and epidemiological profile that attests to the context of social vulnerability of the affected population, requiring integrated actions of rehabilitation that go beyond the physical aspect of their dwellings, since they need to contemplate the human and social development of these people in the broad sense